Investigating the Effect of Humor Therapy on Chronic Pain in the Elderly Living in Nursing Homes in Mashhad, Iran - Shohre behrouz; Seyed Reza Mazlom; Hadi Kooshiar; Nahid Aghebati; Negar Asgharipour; Hamidreza Behnam (Mashhad University of Medical Sciences, 2017)
Background: The prevalence of chronic pains in the elderly residing in nursing homes is high, which can bring about social isolation, depression, incidence of disabilities, as well as increased costs. Given the risks, medication therapy is not used for the elderly, and non-pharmaceutical methods, such as humor therapy as one of the complementary medicine techniques using thought distraction, have been advocated. Aim: This study aimed to determine the effect of humor therapy on pain intensity in the elderly living in nursing homes in Mashhad, Iran. Method: This two-group, randomized, controlled clinical trial was conducted on two groups of intervention (28 individuals) and control (27 individuals) at two similar nursing homes in Mashhad, Iran, 2016. Humor therapy was performed during six 60-minute sessions (once per week) using humorous methods such as video clip displays, games, music plays, as well as telling funny jokes. Then, pain intensity was measured via the Modified German Version of the Brief Pain Inventory before the study and after the 3rd and 6th sessions of humor therapy. Finally, the data was analyzed using Mann-Whitney U test in SPSS, version 22. Results: The mean ages of the participants in the control and intervention groups were 73.9±4.3 and 73.9±5.8 years, respectively. The results of the Mann-Whitney U test also showed that pain intensity before the study in both groups was homogenous (P=0.15). Moreover, the mean scores of the highest, lowest, and moderate pain intensity after the 3rd (P